Soil Properties, Crop Yield, and Economic Return in Response to Lime Application on Acidic Nitisols of Southern Highlands of Ethiopia - Getahun Haile; Habtamu Berihun; Helina Abera; Agegnehu, Getachew; Mulugeta Lemenih (Wiley, 2023)
Soil acidity is one of the major crop production constraints in the highlands of Ethiopia. Liming is becoming a common practice to amend soil acidity, but its effects on soil properties, crop yield, and farm income are not well studied. In this study, an on-farm liming experiment was conducted for two consecutive years (2020-2021) on acidic Nitisols (pH < 5.5) in Southern Ethiopia. The experiment consisted of six liming rates (control, 2.74, 4.11, 5.48, 6.85, and 8.22 t·ha−1) laid out in a randomized complete block design with three replications. Soil, agronomic, and economic data were collected in 2020 and 2021 cropping seasons and analyzed. The application of lime in the ranges of 2.74–8.22 t·ha−1 increased soil pH by 0.46–1.25 units and reduced exchangeable acidity by 2.02–3.17 units. Higher lime rates of 6.85–8.22 t·ha−1 increased soil pH sharply from 5.22 to 5.99 and 6.46, respectively, but such a rise in soil pH was not proportionally reflected in the yield increment. Higher available phosphorus contents of 7.16 and 6.01 mg·kg−1 were measured at the liming rates of 4.11 and 5.48 t·ha−1, respectively. Combined over the two years, 5.45 t·ha−1 lime application yielded the highest barley total biomass of 19,199 kg·ha−1 and a grain yield of 4,328 kg·ha−1, which are 46% and 30% higher than those of the control, respectively. It also yielded the highest marginal rate of return of 477% and a gross margin of 192,857.3 ETB1·ha−1, which is 53% higher than the control. Based on our results, 5.45 t·ha−1 of lime appears to have the optimal rate for economically viable barley production in the study area or similar environments.